2016
DOI: 10.1242/jeb.149211
|View full text |Cite
|
Sign up to set email alerts
|

Retinal specialization through spatially varying cell densities and opsin coexpression in cichlid fish

Abstract: The distinct behaviours of animals and the varied habitats in which animals live place different requirements on their visual systems. A trade-off exists between resolution and sensitivity, with these properties varying across the retina. Spectral sensitivity, which affects both achromatic and chromatic (colour) vision, also varies across the retina, though the function of this inhomogeneity is less clear. We previously demonstrated spatially varying spectral sensitivity of double cones in the cichlid fish Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 56 publications
4
67
0
Order By: Relevance
“…Different visual pigments may be co‐expressed within the same photoreceptor and mixed to differing amounts, potentially to broaden or tune spectral sensitivity or representing transition phases in lifecycle (Lythgoe, ; Hawryshyn & Harosi, ; Hawryshyn et al ., ). For instance, in fresh water, cichlids were found to co‐express cone opsins in both their single (Dalton et al ., ) and double cones (Dalton et al ., ) resulting in broadened spectra to potentially increase achromatic contrast detection. Also, marine fishes such as the yellowfin tuna Thunnus albacares (Bonnaterre 1788) (Loew et al ., ) and starry flounder, Platichthys stellatus (Pallas 1787) (Savelli et al ., ) co‐express multiple opsin pigments during development, but the functionality of this remains elusive.…”
Section: Reef Fishes Colour Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different visual pigments may be co‐expressed within the same photoreceptor and mixed to differing amounts, potentially to broaden or tune spectral sensitivity or representing transition phases in lifecycle (Lythgoe, ; Hawryshyn & Harosi, ; Hawryshyn et al ., ). For instance, in fresh water, cichlids were found to co‐express cone opsins in both their single (Dalton et al ., ) and double cones (Dalton et al ., ) resulting in broadened spectra to potentially increase achromatic contrast detection. Also, marine fishes such as the yellowfin tuna Thunnus albacares (Bonnaterre 1788) (Loew et al ., ) and starry flounder, Platichthys stellatus (Pallas 1787) (Savelli et al ., ) co‐express multiple opsin pigments during development, but the functionality of this remains elusive.…”
Section: Reef Fishes Colour Visionmentioning
confidence: 99%
“…For instance, in fresh water, cichlids were found to co-express cone opsins in both their single (Dalton et al, 2017) and double cones (Dalton et al, 2014) resulting in broadened spectra to potentially increase achromatic contrast detection. Also, marine fishes such as the yellowfin tuna Thunnus albacares (Bonnaterre 1788) (Loew et al, 2002) and starry flounder, Platichthys stellatus (Pallas 1787) (Savelli et al, 2018) co-express multiple opsin pigments during development, but the functionality of this remains elusive.…”
Section: Visual Pigment Co-expressionmentioning
confidence: 99%
“…Studies using L. goodei (Fuller & Claricoates, ) and cichlids (Nandamuri et al, ) that have indicated plasticity in opsin expression reported significant changes in opsin transcripts, measured by qPCR, within 3 days of exposure to new light regimes. Changes in LWS opsin transcript expression within cones has also been observed by in situ hybridization in cichlids after 6 months of light treatment (Dalton et al, ) and by immunolabelling of LWS opsin in M. atlantica after 4 months of treatment (Schweikert & Grace, ). Whether these changes had already occurred prior to these sampling events is unknown.…”
Section: Discussionmentioning
confidence: 71%
“…Besides genetically programmed opsin switches that occur during retinal development, studies on black bream Acanthopagrus butcheri (Munro 1949) (Shand et al, ), cichlids (Dalton et al, ; Härer et al, ; Nandamuri et al, ), bluefin killifish Lucania goodei Jordan 1880 (Fuller & Claricoates, ), guppies Poecilia reticulata Peters 1859 (Sakai et al, ) and Atlantic tarpon Megalops atlanticus Valenciennes 1847 (Schweikert & Grace, ) have shown plasticity in opsin gene expression in response to changes in the light environment. In guppies (Sakai et al, ) and the M. atlanticus (Schweikert & Grace, ), which seem to upregulate opsin gene products to match the dominant wavelengths of new spectral backgrounds, behavioural and electroretinogram observations suggest enhanced sensitivity to the prevalent spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Cone‐specific proportional expression | Proportional normalization for the opsins was also employed using cone type‐specific normalization for single cones (SC: SWS1, SWS2A, SWS2B ) and double cones (DC: RH2A, RH2B, LWS ), calculated as a per cent of all opsins within that cell type. Although localization of opsin expression by cone type is not known specifically for this species, microspectrophotometry and fluorescent in situ hybridization done in other African cichlids have all shown this opsin expression pattern in the single and double cones (Carleton et al, ; Dalton et al, ; Dalton, Loew, Cronin, & Carleton, ). The fraction of single cone opsins made up by a particular opsin is:fopsin,SC=TopsinTSWS1+TSWS2B+TSWS2A…”
Section: Methodsmentioning
confidence: 97%